Motivations for Chinese and Japanese Young Female Consumers to Purchase Luxury Fashion Products: A Cross-cultural Comparison - YU, ZEQUN (2013)
This dissertation aims to answer two main research questions. First, what are the luxury fashion product purchasing motivations of Chinese and Japanese young female consumers? Second, are there any similarities and differences between Chinese and Japanese in their motivations for buying luxury fashion items?